2004
DOI: 10.1152/ajprenal.00414.2003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α-mediated events promote sex-specific diabetic glomerular hypertrophy

Abstract: differences in the incidence and progression of renal diseases suggest a protective role for estrogen. This study examined the role of estrogen receptor ␣ (ER␣)-mediated events in normal and diabetic renal and glomerular growth. Wild-type and ER␣-null mice (ERKO) were observed over 2 wk of streptozocin-induced diabetes. Blood glucose was monitored, and insulin was given daily to maintain levels of 250 -350 mg/dl. Body weight, kidney weight, glucose, insulin, renal transforming growth factor-␤1, and glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
2
33
3
Order By: Relevance
“…31 These observations suggest that estradiol and progesterone in diabetic subjects may be of extratesticular origin, such as the adrenal gland 32 or even the kidney itself. 33 Despite the fact that previous studies from this and other laboratories demonstrated renoprotective effects of estradiol in female diabetic rats, 10,11,34,35 the present study does not support the concept of the beneficial effects of estradiol in the diabetic males, because estradiol levels were elevated with diabetes, coinciding with increases in albuminuria and renal pathology. What the present study demonstrates is that it is not the absolute level of sex hormones that correlates with the severity of the disease but rather the ratio of testosterone/estradiol and testosterone/progesterone.…”
Section: Discussioncontrasting
confidence: 95%
“…31 These observations suggest that estradiol and progesterone in diabetic subjects may be of extratesticular origin, such as the adrenal gland 32 or even the kidney itself. 33 Despite the fact that previous studies from this and other laboratories demonstrated renoprotective effects of estradiol in female diabetic rats, 10,11,34,35 the present study does not support the concept of the beneficial effects of estradiol in the diabetic males, because estradiol levels were elevated with diabetes, coinciding with increases in albuminuria and renal pathology. What the present study demonstrates is that it is not the absolute level of sex hormones that correlates with the severity of the disease but rather the ratio of testosterone/estradiol and testosterone/progesterone.…”
Section: Discussioncontrasting
confidence: 95%
“…Similar observations were made in experimental models of type 1 DM. 40,41 Further supporting the link between sex hormones and diabetes are the observations that women with type 1 DM have impaired ovarian function, delayed age at menarche, are at a higher risk for having menstrual irregularities, and have a higher risk of adverse pregnancy outcomes (eg, spontaneous abortions, stillbirths, and congenital anomalies) than age-matched nondiabetic women. 37,42,43 These observations suggest that type 1 DM is associated with dysregulation of sex hormones, and it is conceivable that reduced estradiol concentrations may be responsible for the loss of female sex as a protective factor, at least in type 1 DM.…”
Section: Nephropathy Sex Hormones and Diabetesmentioning
confidence: 99%
“…Similar to humans, treatment with raloxifene in experimental models attenuated albuminuria and the renal structural damage associated with diabetes. 62,63 Experimental studies also indicate that estrogen receptor α is abnormally regulated in the diabetic kidney 40,41 and, coupled with the abnormal regulation of its ligand, 40,41 contributes to the progression of diabetic renal disease. Indeed, a recent study reported an association between introns 1 and 2 of the estrogen receptor-α gene and diabetic nephropathy in African-American and European-American populations, 64 further stressing the potential importance of sex hormones and their receptors in the pathophysiology of diabetic nephropathy.…”
Section: Estrogens and Diabetic Nephropathymentioning
confidence: 99%
“…We have recently reported that female mice lacking estrogen receptor-␣ (ERKO) are protected from diabetic glomerular hypertrophy, although not from overall diabetic kidney growth (19). Differences in kidney weight were noted in nondiabetic mice, suggesting that this genotype also altered normal kidney development.…”
mentioning
confidence: 99%